2016
DOI: 10.18512/1980-6477/rbms.v15n3p386-397
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL RISK OF LOSSES IN MAIZE CAUSED BY Dichelops melacanthus (DALLAS) (HEMIPTERA: PENTATOMIDAE) IN BRAZIL

Abstract: ABSTRACT:The incidence of the green belly stink bug, Dichelops melacanthus (Dallas) (Heteroptera: Pentatomidae), on maize crop in Brazil has increased with time, especially due to the continuous availability of food throughout the year. This insect causes injury to seedlings, killing them shortly after their emergence from the soil. If the plant survives, it is possible to see areas with necrotic lesion that increase in a transverse pattern on the sheet, with perforations on the leaves or tillers (side shoots)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
4
0
3
Order By: Relevance
“…Roza-Gomes et al ( 2011) observed a mean injury score of 2.8 using the density of five stink bugs infested on five maize plants, starting from the V1 stage. In the present study, the use of the injury rating scale modified from maize evaluation was an efficient method to detect differences in susceptibility to GBS between the sorghum hybrids (Roza-Gomes et al, 2011;Duarte et al, 2015;Bridi et al, 2016;Cruz et al, 2016). Therefore, its use can be recommended in future studies evaluating resistance to GBS in grain sorghum.…”
Section: Discussionmentioning
confidence: 76%
“…Roza-Gomes et al ( 2011) observed a mean injury score of 2.8 using the density of five stink bugs infested on five maize plants, starting from the V1 stage. In the present study, the use of the injury rating scale modified from maize evaluation was an efficient method to detect differences in susceptibility to GBS between the sorghum hybrids (Roza-Gomes et al, 2011;Duarte et al, 2015;Bridi et al, 2016;Cruz et al, 2016). Therefore, its use can be recommended in future studies evaluating resistance to GBS in grain sorghum.…”
Section: Discussionmentioning
confidence: 76%
“…También se ha detectado que una infestación de 3,16 chinches da lugar a una disminución de cerca del 12 % en el largo de la espiga en relación con el tamaño de la espiga sin presencia del insecto. Asimismo, un trabajo similar describe que sin la presencia del insecto el rendimiento del grano de maíz fue de 8.048,43 kg/ha, mientras que, con el insecto, fue de 6.352,21 kg/ha, una diferencia de 21,07 % o 1.696,22 kg/ha (Cruz et al, 2016). (Bortolotto et al, 2016).…”
Section: Discussionunclassified
“…Embora estudos apresentem valores divergentes quanto ao impacto de percevejos na fase inicial do milho (CHIARADIA et al, 2016;GOMES et al, 2020), o nível de dano econômico (NDE) atualmente preconizado para percevejos adultos de barriga-verde na fase inicial da cultura do milho situase sempre abaixo de 0,5 percevejo/m de plantas, considerando o impacto da praga na produtividade da cultura, os valores atuais do cereal no mercado e os custos de controle da praga. Todavia, há marcantes variações na suscetibilidade dos genótipos de milho disponíveis no mercado (CROSARIOL NETTO et al, 2015;CRUZ et al, 2016), especialmente quanto à expressão da resistência do tipo tolerância. Além disso, níveis diferenciados de adubação de cobertura podem, em hipótese, mitigar o impacto dos danos de percevejos na fase inicial da cultura, fato em investigação na Epagri/Cepaf.…”
Section: Danos E Período Crítico De Ocorrênciaunclassified
“…Por constituir em uma praga de sistemas, o adequado manejo em culturas antecessoras, como soja, cereais de inverno e plantas de cobertura ou infestantes (Figura 2A), reduz a população de percevejos nas áreas e o impacto na fase inicial do milho. Além disso, a adoção de boas práticas agrícolas, como a dessecação antecipada e o manejo de plantas voluntárias (CRUZ et al, 2016), são medidas de manejo cultural importantes.…”
Section: Estratégias De Manejounclassified